Расчёт распределения потока жидкости в трубчатке кожухотрубного теплообменного аппарата - Николаев А. В. Александр Валерьевич; Шелопугин Д. С. Дмитрий Сергеевич; Криницын Н. С. Николай Станиславович; Дядик В. Ф. Валерий Феодосиевич (2017, 2017)
Заглавие с экрана